Analysis of the Influence of Profitability and Solvency on Stock Prices at PT Bank Ina Perdana Tbk. - Rosmawati, Siti; Yulianingsih, Yulianingsih (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study utilizes information from the company's annual financial report to examine the relationship between profitability and solvency with the stock price of PT Bank Ina Perdana Tbk during the period 2019-2023. (ROA) Return on Asset is applied to assess profitability and (DER) Debt to Equity Ratio is applied to assess solvency. Multiple linear regression analysis is the quantitative strategy used. The results of the study reveal that both in simultaneous and partial aspects, profitability and solvency do not have a significant impact on the stock price of PT Bank Ina Perdana Tbk. This study provides insight even though both variables are important in financial performance analysis, however, during the study period the stock price was not directly influenced by ROA and DER. Keywords :Profitability, Solvency, Stock Price.